Modeling of coupled phase transformation and reorientation in shape memory alloys under non-proportional thermomechanical loading. (July 2016) - Chatziathanasiou, Dimitris; Chemisky, Yves; Chatzigeorgiou, George; Meraghni, Fodil
Abstract: In the present study, a new 3D thermodynamic coupled model is proposed for SMAs. The behavior of SMA structures is described through several strain mechanisms, each associated with its proper internal variables. This model is built to capture the particular behavior of SMAs when subjected to complex loading, namely non-proportional thermomechanical loading. To achieve this task, a new approach to describe the martensitic reorientation mechanism has been introduced in conjuction with a new method to account for forward and reverse transformation. Thermomechanical coupling, related to dissipation and latent heat is fully implemented. The validity of the model is demonstrated by comparing experimental results of complex thermomechanical loading paths of SMA structures with numerical simulations. Highlights: A new 3D phenomenological model for SMAs is introduced accounting for reorientation. It is built to capture material behavior under complex non-proportional loading. Inelastic strain mechanisms are rigorously described in the meso- and macro-scale. The thermomechanical aspects of the coupled modelisation is fully investigated. Existing experiments of complex loading paths have been numerically simulated.